1981
DOI: 10.1002/ajpa.1330550209
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin variations on a small bahamian island

Abstract: Hemoglobino characteristic were investigated in 492 blood specimens collected in a small island community (1,450 inhabitants) in the Bahamas. Using two different methods, abnormal variants were detected in 20.3% of the sample, including genotypes AS, AC, AF(A/HPFH), SC, and SF. Biodemographic evidence suggests that the origin and distribution of the hemoglobinpathies in this population have been influenced by historical migrations and genetic drift. The opportunity for drift has been particularly heightened by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…The considerable proportion (ranging from 71.2% to 79.7%) of haplogroup A1b‐V152, B‐M60, E1a‐M33, E1b1a‐M2, and E2b‐M98 lineages in the Bahamian paternal gene pool (with the exception of the Long Island population), signals a direct genetic connection with continental Africa, consistent with earlier reports based on classical (Halberstein et al,1981) and autosomal STR (Herrera et al,2004; Simms et al,2008,2010,2011) markers. Genetic affinities between the Bahamas and continental Africa, which are also observed in the MDS (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The considerable proportion (ranging from 71.2% to 79.7%) of haplogroup A1b‐V152, B‐M60, E1a‐M33, E1b1a‐M2, and E2b‐M98 lineages in the Bahamian paternal gene pool (with the exception of the Long Island population), signals a direct genetic connection with continental Africa, consistent with earlier reports based on classical (Halberstein et al,1981) and autosomal STR (Herrera et al,2004; Simms et al,2008,2010,2011) markers. Genetic affinities between the Bahamas and continental Africa, which are also observed in the MDS (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the moderate amount of genetic data available for the Caribbean and other New World populations, the islands of the Bahamas remain virtually unexplored genetically, with only a few phylogenetic and evolutionary studies on the island chain reported thus far. These investigations, which are based exclusively on classical (Halberstein et al,1981) and autosomal STR (Duncan etal.,1996; Budowle et al,1999; Herrera et al,2004; Simms et al,2008,2010,2011) polymorphisms, reveal substantial gene flow from continental Africa and varying degrees of genetic input from European, East Asian and Native American ancestors. In this article, we explore, for the first time, the paternal genetic histories of six Bahamian islands and their relationships with previously published reference collections using high‐resolution Y‐chromosome binary markers.…”
mentioning
confidence: 99%
“…The considerable proportion (ranging from 71.2% to 79.7%) of haplogroup A1b-V152, B-M60, E1a-M33, E1b1a-M2, and E2b-M98 lineages in the Bahamian paternal gene pool (with the exception of the Long Island population), signals a direct genetic connection with continental Africa, consistent with earlier reports based on classical (Halberstein et al, 1981) and autosomal STR Simms et al, 2008Simms et al, , 2010Simms et al, , 2011 markers. Genetic affinities between the Bahamas and continental Africa, which are also observed in the MDS (Fig.…”
Section: Discussion Genetic Signatures Of the Transatlantic Slave Tradesupporting
confidence: 84%
“…These investigations, which are based exclusively on classical (Halberstein et al, 1981) and autosomal STR (Duncan et al, 1996;Budowle et al, 1999;Herrera et al, 2004;Simms et al, 2008Simms et al, , 2010Simms et al, , 2011 polymorphisms, reveal substantial gene flow from continental Africa and varying degrees of genetic input from European, East Asian and Native American ancestors. In this article, we explore, for the first time, the paternal genetic histories of six Bahamian islands and their relationships with previously published reference collections using highresolution Y-chromosome binary markers.…”
mentioning
confidence: 99%